Identification of aluminum resistant Andean common bean (Phaseolus vulgaris L.) genotypes - Blair, Matthew W.; López Marin, H.D.; Rao, Idupulapati M. (FapUNIFESP, 2009)
Aluminum (Al) toxicity is the principal abiotic constraint in acid soils of the tropics. Common bean, meanwhile, is for the most part very sensitive to this stress although certain genotypes within the species show some level of resistance, justifying screening of germplasm from both the Andean and Mesoamerican genepools to identify better performing sources. The objective of this study was to evaluate 36 genotypes of common bean under hydroponic conditions to identify root morphological traits that could be associated with Al resistance. A total of five root traits (elongation rate of the primary root, total root length, root biomass, average root diameter and specific root length) were measured using a simple nutrient solution with or without Al (20 ?M) over a 48 hour growth period with the experiments conducted in five replicates. We found that genotypes from the Andean gene pool were more resistant to Al than Mesoamerican genotypes under these conditions, based on a smaller decrease in the elongation rate of the primary root, total root length, specific root length and a lesser increase in root diameter in the presence of Al in nutrient solution. These root traits but not root biomass can serve as selection criteria to distinguish between Al-resistant and Al-sensitive genotypes.